Combined flow-based imaging assessment of optimal cardiac resynchronization therapy pacing vector: a case report - Martiniello, A. R. (J Med Case Rep, 2019)
BACKGROUND: There are still many pendent issues about the effective evaluation of cardiac resynchronization therapy impact on functional mitral regurgitation. In order to reduce the intrinsic difficulties of quantification of functional mitral regurgitation itself, an automatic quantification of real-time three-dimensional full-volume color Doppler transthoracic echocardiography was proposed as a new, rapid, and accurate method for the assessment of functional mitral regurgitation severity. Recent studies suggested that images of left ventricle flow by echo-particle imaging velocimetry could be a useful marker of synchrony. Echo-particle imaging velocimetry has shown that regional anomalies of synchrony/synergy of the left ventricle are related to the alteration, reduction, or suppression of the physiological intracavitary pressure gradients. CASE SUMMARY: We describe a case in which the two technologies are used in combination during acute echocardiographic optimization of left pacing vector in a 63-year-old man, Caucasian, who showed worsening heart failure symptoms a few days after an implant, and the effect of the device’s optimization at 6-month follow-up. DISCUSSION: The degree of realignment of hemodynamic forces, with quantitative analysis of the orientation of blood flow momentum (φ), can represent improvement of fluid dynamics synchrony of the left ventricle, and explain, with a new deterministic parameter, the effects of cardiac resynchronization therapy on functional mitral regurgitation. Real-time three-dimensional color flow Doppler quantification is feasible and accurate for measurement of mitral inflow, left ventricular outflow stroke volumes, and functional mitral regurgitation severity. CONCLUSION: This clinical case offers an innovative and accurate approach for acute echocardiographic optimization of left pacing vector. It shows clinical utility of combined three-dimensional full-volume color Doppler transthoracic echocardiography/echo-particle imaging velocimetry assessment to increase response to cardiac resynchronization therapy, in terms of reduction of functional mitral regurgitation, improving fluid dynamics synchrony of the left ventricle. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13256-019-2048-1) contains supplementary material, which is available to authorized users.